Adiabatic excitation for 31P MR spectroscopy in the human heart at 7 T: A feasibility study. Issue 5 (21st December 2016) - Valkovič, Ladislav; Clarke, William T.; Purvis, Lucian A.B.; Schaller, Benoit; Robson, Matthew D.; Rodgers, Christopher T.
Abstract : Purpose: Phosphorus magnetic resonance spectroscopy ( 31 P‐MRS) provides a unique tool for assessing cardiac energy metabolism, often quantified using the phosphocreatine (PCr)/adenosine triphosphate (ATP) ratio. Surface coils are typically used for excitation for 31 P‐MRS, but they create an inhomogeneous excitation field across the myocardium, producing undesirable, spatially varying partial saturation. Therefore, we implemented adiabatic excitation in a 3D chemical shift imaging (CSI) sequence for cardiac 31 P‐MRS at 7 Tesla (T). Methods: We optimized an adiabatic half passage pulse with bandwidth sufficient to excite PCr and γ‐ATP together. In addition, the CSI sequence was modified to allow interleaved excitation of PCr and γ‐ATP, then 2, 3‐DPG, to enable PCr/ATP determination with blood correction. Nine volunteers were scanned at 2 transmit voltages to confirm that measured PCr/ATP was independent of B 1 + (i.e. over the adiabatic threshold). Six septal voxels were evaluated for each volunteer. Results: Phantom experiments showed that adiabatic excitation can be reached at the depth of the heart using our pulse. The mean evaluated cardiac PCr/ATP ratio from all 9 volunteers corrected for blood signal was 2.14 ± 0.16. Comparing the two acquisitions with different voltages resulted in a minimal mean difference of − 0.005. Conclusion: Adiabatic excitation is possible in the human heart at 7 T, and gives consistent PCr/ATP ratios. Magn Reson Med 78:1667–1673, 2017. © 2016 The Authors Magnetic Resonance in Medicine published by Wiley Periodicals, Inc. on behalf of International Society for Magnetic Resonance in Medicine. This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.